Upaya Peningkatan Elektabilitas Calon Bupati Perempuan dalam Pemilihan Kepala Daerah Kabupaten Kudus Tahun 2018 - Umi Qodarsasi; Nevy Rusmarina Dewi2 (MUWAZAH : jurnal kajian gender, 2019)
Since the Regional Head Election was openly held, the community had a great opportunity to elect the candidates directly. In addition, with the openness of the elections, the community can actively nominate themselves as deputy regional heads, both men and women. Women not only participate at the legislative level, but also become candidates for regent / deputy regent and governor / deputy governor. This study focuses on the nomination of awoman candidate in the Regional Election of Kudus in 2018 and how the efforts of woman candidates to increase their electability. The method and approach used in this qualitative- descriptive assessment with data collection is done through interviews and literature studies. Kudus Regency is seen as a prospective area for woman regional head candidates because of the large woman population. The ratio of the number of man and woman populations obtained by 96.99, which shows that for every 100 woman residents there are 97 man residents. The same thing happened in every sub-district in Kudus Regency which has a sex ratio ranging from 94.24 to 98.30. In winning the vote, the woman candidate, Sri Hartini, made the election as a place to get an opportunity to be able to lead Kudus. Various strategies to increase votes through political campaigns were carried out. The use of women's identity as an effort to increase electability in the elections. Sri Hartini focused on the issue of gender equality and women's empowerment, she presented this by representing herself as a woman who was independent and empowered and able to compete with men. He believes he is capable of working in Kudus because there are more women in Kudus than men.